A CLASS STRUGGLE IN THE INDUSTRIAL REVOLUTION ERA IN NINETEETH CENTURY OF CHARLES DICKENS’S NOVEL “OUR MUTUAL FRIENDS” - Megah, Suswanto Ismadi (JURNAL DIMENSI, 2013)
This novel tells the poor condition during the industrial revolution due to the power new industrialist who sweep the small scale enterprenours. Dickens himslef views his society as the bad condition because the power only owned by the rich group only. He criticizes poverty in his society and class strugle by using his writing in his novels. In “Our Mutual Friend” told that everyone needs money to survive as the money is the power to do something in the greatly-different class. Eventually, Dickens tells that the upper and the lower class need each others and live harmoniously as he expects.